Answer:
w = 2
Step-by-step explanation:
Distribute the expression and compare like terms with the simplified version.
Given
wx(3y² + 6y - 2) ← distribute parenthesis
= 3wxy² + 6wxy - 2wx
Compare coefficients of like terms with
6xy² + 12xy - 4x
Compare xy² term, then
3w = 6 ( divide both sides by 3 )
w = 2
Compare xy term, then
6w = 12 ( divide both sides by 6 )
w = 2
Compare x term, then
- 2w = - 4 ( divide both sides by - 2 )
w = 2
Hence the required value of w is 2
So hmm notice the picture below
you're simply being asked to, approximate the area, by using 4 rectangles, like in the graph, it doesn't have to be an exact value, just an approximation, based on the width and height of the rectangles, and getting their area by that
those rectangles are 0.39 radian long, since if you split π/2 in 4 pieces, you get around that much, the last rectangle there is a bit smaller than 0.39.... but they don't have to be 4 rectangles of equal length
so, get the area of the rectangles, based on their width and height, and sum them up
Answer:
80.2
Step-by-step explanation:
Answer:
large = 18 3/4 = 18.75
small = 13/2 = 6 1/2 = 6.5
Step-by-step explanation:
Let l = the weight of large boxes
s = weight of small boxes
2 large and 3 small weights 57
2l+3s = 57
6 large and 5 small wights 145
6l+5s = 145
Multiply the first equation by 3
3(2l+3s) = 57*3
6l +9s =171
Subtract the second equation
6l +9s =171
-6l -5s = -145
-----------------------
4s =26
Divide each side by 4
4s/4 = 26/4
s = 26/4 = 13/2
Substitute this into the first equation
2l +3s = 57
2l + 3(13/2) =57
Multiply by 2 to get rid of the fractions
2(2l + 3(13/2)) =57*2
4l + 39 = 114
Subtract 39 from each side
4l +39-39 = 114-39
4l =75
Divide by 4
4l/4 = 75/4
l = 75/4 = 18 3/4
Answer:
none of them
Step-by-step explanation:
Two lines are perpendicular when satisfy the next equation: m1*m2 = -1, where m1 and m2 are the slopes o the lines.
line 1:
y – 1 = (x+2)
y = x + 3
slope of line 1 = 1
line 2:
y + 2 = –3(x – 4)
y + 2 =
-3*x + 12
y = -3*x + 10
slope of line 2 = -3
m1*m2 = 1*(-3
) = -3
They are not perpendicular
line 3:
y − 5 = 3(x + 11)
y − 5 = 3*x + 33
y = 3*x + 38
slope of line 3 = 3
m1*m3 = 1*3 = 3
They are not perpendicular
line 4:
y = -3x –
slope of line 4 = -3
m1*m4 = 1*(-3
) = -3
They are not perpendicular
line 5:
y = x – 2
slope of line 5 = 1
m1*m5 = 1*1 = 1
They are not perpendicular
line 6:
3x + y = 7
y = -3x + 7
slope of line 6 = -3
m1*m6 = 1*(-3
) = -3
They are not perpendicular